Community re-education on the urgency of keeping the river clean and sorting waste in Desa Cikole Kec. Lembang - Rachmat Ichwan Nurdin; Hafsah Nugraha; Isye Iswari Arbie; Salma Almira Hamdani; Rizza Lestari; Ilvira Khoerunnisa; Rima Rachmawati; Tina Aprilia; Muhammad Vidia Adhiyaksa; Romi Samsuhardo; Billy Idan Setiadi; Mupid Hidayat (Universitas Pendidikan Indonesia, 2023)
Lembang area is one of the contributors to water pollution in the Cibeureum and Cikapundung rivers which empties into the Citarum river. One of the things that pollute it is animal waste because some residents habitually throw it directly into the river. The program's dedication in the form of Kuliah Kerja Nyata (KKN), published in this article, aims to increase the awareness of residents and students about the importance of sorting and processing waste. Also, providing education that maintaining cleanliness in Cikole has helped reduce the problem of the Citarum river. It includes education about composting as a way to process animal manure. The method used is value planting and a synergy approach. Some of the programs carried out are the Harum Citarum Seminar by the TNI SATGAS, river carcasses, composting, making organic, inorganic, and B3 trash cans, social services or cooperation, and the commemoration of the Republic of Indonesia's anniversary. After implementing the program, most residents and school students realized the importance of protecting the environment, as seen by the amount of waste disposed of carelessly in several areas. The community has also understood the importance of keeping the environment clean, especially around the river. Abstrak Daerah Lembang merupakan salah satu penyumbang pencemaran air di sungai Cibeureum dan Cikapundung yang mengalir sampai sungai Citarum. Salah satu yang mencemarinya adalah kotoran hewan, karena beberapa warga memiliki kebiasaan membuang langsung kotoran hewan ke aliran sungai. Program pengabdian dalam bentuk Kuliah Kerja Nyata (KKN) yang dimuat dalam tulisan ini bertujuan untuk meningkatkan kesadaran warga dan juga peserta didik tentang pentingnya memilah dan mengolah sampah. Juga memberikan edukasi bahwa dengan menjaga kebersihan di Cikole telah membantu mengurangi masalah sungai Citarum. Memberikan edukasi tentang pembuatan kompos sebagai salah satu cara mengolah kotoran hewan. Metode yang digunakan adalah pendekatan penanaman nilai dan sinergitas. Beberapa program yang dijalankan yaitu Seminar Citarum Harum oleh SATGAS TNI, karbak sungai, pembuatan kompos, pembuatan tong sampah organik, anorganik, dan B3, kerja bakti atau gotong royong, dan peringatan HUT RI. Setelah program dilaksanakan, sebagian besar warga dan siswa sekolah telah menyadari akan pentingnya menjaga lingkungan terlihat dari kuantitas sampah yang dibuang sembarangan semakin sedikit di beberapa daerah. Masyarakat juga telah diberikan pemahaman akan pentingnya menjaga kebersihan lingkungan terutama lingkungan sekitar sungai. Kata Kunci: Pembinaan pemilahan sampah; pembinaan pencegahan pencemaran sungai; program Citarum Harum; re-edukasi masyarakat.